COMPARATIVE ANALYSIS OF THE EFFECTIVENESS AND CONTRIBUTION OF LOCAL TAXES IN THE TOURISM SECTOR BEFORE AND DURING COVID-19 (Study on Regency and City of Central Java Province) - Maula Zaenal Abidin; Ekaningtyas Widiastuti; Najmudin Najmudin (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
The objective of this study is to investigate and analyze the variations in the effectiveness and impact of local tax revenues from districts and cities in Central Java, both before and during the COVID-19 pandemic. The study focuses on six specific variables, namely the effectiveness and contribution of Hotel Tax, Restaurant Tax, and Entertainment Tax. The study population consists of all the regencies and cities in Central Java from the years 2018 to 2021, and a saturated sample is used, meaning that all available data is included in the analysis. A total of 35 samples, comprising of 29 regencies and six towns, are included in the analysis. To conduct this research, a quantitative approach is employed, specifically using a paired t-test analysis of panel data. The analysis is carried out using SPSS analysis tools, which allow for the examination of the differences and similarities in the effectiveness and impact of the different tax revenues before and during the COVID-19 period. The findings of this study reveal significant disparities in the effectiveness of Entertainment Tax, as well as the contributions of Hotel Tax, Restaurant Tax, and Entertainment Tax, before and during the COVID-19 period. This suggests that the pandemic has had a significant impact on the efficacy and impact of these tax revenues in Central Java. However, no significant differences were observed in the effectiveness of Hotel Tax and Restaurant Tax, indicating that these taxes have remained relatively stable and unaffected by the pandemic.